2016
DOI: 10.1177/1558944715626925
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Outcomes Following a Randomized Controlled Trial of Dynamic Splint Stretching for Carpal Tunnel Syndrome

Abstract: Background: The incidence of carpal tunnel syndrome (CTS) is 48 million patients in the United States. The purpose of this longitudinal study was to determine whether Dynasplint stretching (immediately after diagnosis) had an effect on a patient's decision to seek surgical treatment for CTS. Methods: Fifty patients (10 men, 40 women, mean age 51.2 ± 12 years) were recruited for this randomized, controlled, longitudinal trial. Patients were diagnosed with CTS by physical examination and nerve conduction studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Nine randomized controlled trials [6][7][8][9][10][11][12][13][14] have compared the effectiveness of orthoses with other conservative treatments for CTS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine randomized controlled trials [6][7][8][9][10][11][12][13][14] have compared the effectiveness of orthoses with other conservative treatments for CTS.…”
Section: Resultsmentioning
confidence: 99%
“…Among the nine studies [6][7][8][9][10][11][12][13][14] included in the review, three [6,8,12] compared the efficacy of injection therapy and splints and one [9] investigated the efficacy of two different types of splints. In addition, two studies [7,11] compared the effects of splints with and without other conservative therapies, and one [13] compared the effects of injection therapy alone with those of combined injection and splinting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main rationale behind the use of splints in CTS patients is the prevention of extensive flexion and extension of the wrist that causes an increase in the pres- sure inside the carpal tunnel. Sixty days of using a stretch- ing splint has been known to reduce the need for surgery 2 to 1 compared to stretching and NSAIDs [ 80 ]. Splints are also commonly used after surgical retinaculum release where they theoretically provide safety regarding flexor tendon bowstringing to prevent nerve subluxation and thus reduce postoperative pain.…”
Section: Conservative Treatmentmentioning
confidence: 99%
“…They further explained that the longer the finger; the greater the spring tension exerted on the tendon of the finger [36]. In a study by Willis et al [37] it was suggested that a dynamic splint should offer a prolonged duration of inactive; joint precise stretching with small-load power.…”
Section: The Mechanical Forces Within the Dynamic Splintmentioning
confidence: 99%